Greece & Turkey; Assessment and Comparison of Their Renewable Energy Performance - Menegaki, Angeliki N; Gurluk, Serkan (International Journal of Energy Economics and Policy, 2013)
This paper is a comparative review of the renewable energy performance of Turkey and Greece. Both neighboring countries sharing the same energy hub with a large potential for renewable energy production. Albeit having strikingly similar energy objectives and hindrances, they are currently challenged by different contexts. Turkey, although not a European Union member, it spends efforts to tacitly comply with European Union legislation and sets ambitious renewable energy targets. Greece on the other hand is afflicted by an economic crisis that threatens to retard its renewable energy developments unless Greece uses renewable energy sources as a means to escape the crisis. This paper is useful for potential renewable energy investors in the area of Greece and Turkey. Keywords: Greece; renewable energy sources; Turkey JEL Classifications: O13; O57; Q28